Effectiveness of an SMS-based maternal mHealth intervention to improve clinical outcomes of HIV-positive pregnant women. Issue 7 (3rd July 2017) - Coleman, Jesse; Bohlin, Kate C.; Thorson, Anna; Black, Vivian; Mechael, Patricia; Mangxaba, Josie; Eriksen, Jaran
ABSTRACT: We conducted a retrospective study to investigate the effectiveness of an mHealth messaging intervention aiming to improve maternal health and HIV outcomes. Maternal health SMSs were sent to 235 HIV-infected pregnant women twice per week in pregnancy and continued until the infant's first birthday. The messages were timed to the stage of the pregnancy/infant age and covered maternal health and HIV-support information. Outcomes, measured as antenatal care (ANC) visits, birth outcomes and infant HIV testing, were compared to a control group of 586 HIV-infected pregnant women who received no SMS intervention. Results showed that intervention participants attended more ANC visits (5.16 vs. 3.95, p < 0.01) and were more likely to attend at least the recommended four ANC visits (relative risk (RR): 1.41, 95% confidence interval (CI): 1.15–1.72). Birth outcomes of intervention participants improved as they had an increased chance of a normal vaginal delivery (RR: 1.10, 95% CI: 1.02–1.19) and a lower risk of delivering a low-birth weight infant (<2500 g) (RR: 0.14, 95% CI: 0.02–1.07). In the intervention group, there was a trend towards higher attendance to infant polymerase chain reaction (PCR) testing within six weeks after birth (81.3% vs. 75.4%, p = 0.06) and a lower mean infant age in weeks at HIV PCR testing (9.5 weeks vs. 11.1 weeks, p = 0.14). These results add to the growing evidence that mHealth interventions can have a positive impact on health outcomes and should be scaled nationally following comprehensive evaluation.